Enhancing Learning Through Technology. Education Unplugged: Mobile Technologies and Web 2.0 6th International Conference, ITC 2011, Hong Kong, China, July 11-13, 2011. Proceedings - Kwan, Reggie; McNaught, Carmel; Tsang, Philip; Wang, Fu Lee.; Li, Kam Cheong; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the International Conference on ICT in Teaching and Learning, ICT 2011, jointly held in Hong Kong, China, in July 2011 with the 15th Hong Kong Web Symposium. The 30 revised full papers presented were carefully reviewed and selected from numerous submissions. The papers present current research on innovative and effective usage of social networking, multimedia and mobile learning technologies. Topics addressed are such as: emerging pedagogies, mobile technologies, Web 2.0, social networking, bookmarking and repository communities, e-learning, mobile and distributed learning, social computing mobile learning system design and architecture semantic Web applications d-learning, e-learning, m-learning education environments privacy, risk, and security.
Keywords: Computer science; Computer Communication Networks; Computer software; Information storage and retrieval systems; Information systems; Artificial intelligence; Computer Science; Information Systems Applications (incl.Internet).; Artificial Intelligence (incl. Robotics).; Algorithm Analysis and Problem Complexity; Computer Communication Networks; User Interfaces and Human Computer Interaction; Information Storage and Retrieval